The Representation of the Social and Political Reality in the Palestinian Cinema: Mashrawi's film "Laila's Birthday": - Alraee, Ghada Hamdi (Journal of Humanities & Social Sciences, 2023)
The Cinema is an important cultural tool that is used by Palestinian filmmakers in order to document any violations committed by Israel against their people, track the social and political changes in the occupied Palestinian territories, and draw attention to major problems in the Palestinian society. Then, some films were made to criticize the internal situation. This study discussed "Laila's Birthday", a movie by the Palestinian director Rashid Masharawi, to show how the social and political reality is represented through the cinematic discourse. It is a descriptive analytical study. The film depicted the breakdown of the social order ​​in the context of the internal Palestinian divide and the Israeli blocked. The study concluded that Mashrawi's film demythologized the Palestinian society that used to be represented as a revolutionary, homogeneous and heroic society, Also, the study drew attention to the Palestinian cinema aesthetics and its power to address the social problems and express the suffering of the Palestinian people.
Keywords: Cinema; social reality; occupied Palestinian territories; internal Palestinian divide; lawlessness